INVESTIGATIONS ON CERAMIC COATED DIESEL ENGINE WITH BRASS PISTON MATERIAL - Reddy, S. Sunit Kumar; Pandurangadu, V. (Journal of Mechanical Engineering, 2014)
With the enormous energy demand and environmental concern the interest on the alternate fuels tothe diesel engines has been increased. Among all the fuels alcohols have received a considerable attentionbecause these are bio-based, renewable and are oxygenated. But due to its properties they require higheroperating temperatures in the combustion chambers. Hence in the present work a ceramic coated insulatedengine is developed by incorporating an air gap between piston skirt and crown for the study of alcoholsperformance and emission characteristics. The combustion efficiency depends on the mixture strength, pistonmaterial and turbulence in the chamber. So, in this work an attempt is made with brass piston and brass insertwith nine and twelve grooves. Among all the pistons tested the brass insert with nine grooves is best in terms ofengine performance and emissions. With the elevated temperatures the main problems faced are drop involumetric efficiency and lubricating oil deterioration and can be avoided with turbo compounding system andnew lubricants. DOI: http://dx.doi.org/10.3329/jme.v44i1.19492